EFFECTS OF INFORMATION AND COMMUNICATION TECHNOLOGY ADOPTION ON MSMEs IN THE RETAIL SECTOR MARKETING PERFORMANCE IN CIBADUYUT AREA, BANDUNG CITY - Dewanta, Fajar Sukma; Alexandri, Mohammad Benny; Kostini, Nenden (Advances in Social Sciences Research Journal, 2018)
Micro, small and medium enterprises (MSMEs) have become priority for economic development as an effort to increase the competitiveness of MSMEs. Moreover, MSMEs have the potential and also become the driving force of the Indonesian economic development.Cibaduyut area, which is the main center of the textile industry and processing in Bandung City. However, MSMEs in this area have faced great pressure since the enactment of the ASEAN-China Free Trade Area (ACFTA) in 2010. There have been efforts made by businessmen, especially the retail sector in this area to increase the company competition by adopting Information and Communication Technology (ICT). This study aims to find out how the ICT effects on company performance in the retail sector MSMEs in Cibaduyut area, especially towards marketing performance. Respondents in this study were sampled using proportionate stratified random sampling to determine the number of samples based on the size of the business.The analysis technique used is multiple regression analysis using the SPSS 22.0 application. The results showed that there are significant effects between Information Technology, Communication Technology and also between Information Technology and Communication Technology on MSMEs Marketing Performance in the retail sector in Cibaduyut, Bandung City.